Hubungan Perilaku Makan Dan Peran Teman Sebaya Dengan Resiko Anemia Pada Remaja Putri Di SMP Negeri 90 Jakarta - Sinta, (2020)
Anemia is a condition where the value of hemoglobin (Hb) in the blood is lower than the normal value for individuals based on age and sex, in adolescent women the normal hemoglobin level is 12-15 g / dl, in adolescent males, 13- 17 g / dl (Adriani, 2017). The purpose of this study was to determine the relationship of eating behavior and the role of peers with the risk of anemia in adolescent girls at SMP Negeri 90 Jakarta. The design of this research is quantitative with cross sectional approach and used chi square test to analyze the relationship between variables. The population in this study were young women in Jakarta State Junior High School 90 class VII and VIII with a sample of 152 people. The sampling technique used is stratified random sampling. The results showed that there was a relationship between eating behavior and the risk of anemia in adolescent girls at SMP Negeri 90 Jakarta, indicated by a p-value of 0.001. Furthermore, the peer role variable with a p-value of 0.012, which means there is a significant relationship between the role of peers and the risk of anemia in adolescent girls in SMP Negeri 90 Jakarta. So the conclusion is that there is a relationship between eating behavior and the role of peers with the risk of anemia in adolescent girls in SMP Negeri 90 Jakarta.